THE LEGAL CONCEPT OF REPRESENTATION - Marković, Velisav (Law - Theory and Practice, 2014)
Representation refers to taking legal affairs on behalf of the represented individual or legal entity based on the Power (Letter) of Attorney. The Power of Attorney is based on 1. Law; 2. the General Act of the legal entity; 3. the Act of the competent public body; 4. the Statement given by the represented individual. A legal entity may be in a situation not to be able to undertake any legal act by himself/herself, for either legal or factual obstacles. The Institute of representation enables all persons who cannot undertake certain legal acts by themselves, to do it through their empowered representative – agent. Some legal issues are not allowed to be undertaken through a representative-agent. This article gives a review on the legal concept of representation and its essential elements, as well as on the acting in the name and for the account of the represented individual.